2021
DOI: 10.1016/j.sjbs.2020.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical evaluation and anticancer activity of rambutan (Nephelium lappaceum) fruit endocarp extracts against human hepatocellular carcinoma (HepG-2) cells

Abstract: The current investigation was taken to screen the phytoconstituents present in fruit endocarp various extracts of Nephelium lappaceum commonly called as Rambutan fruit and its anticancer property against human hepatocellular carcinoma (HepG-2) cells. Different analytical techniques including qualitative phytochemical analysis, cell viability assay (MTT), apoptotic nuclear staining (DAPI), DNA fragmentation assay, Attenuated total reflection (ATR) and Gas chromatography–mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
0
6
0
4
Order By: Relevance
“…Additionally, the use of high doses of methotrexate has been reported to be toxic to humans [ 2 ] and mice [ 10 ]. These results suggest that IA has antitumoral potential [ 4 , 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the use of high doses of methotrexate has been reported to be toxic to humans [ 2 ] and mice [ 10 ]. These results suggest that IA has antitumoral potential [ 4 , 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the use of high doses of methotrexate has been reported to be toxic to humans [2] and mice [10]. These results suggest that IA has antitumoral potential [4,[11][12][13]. In addition, because DAPI staining was used, the strong cytotoxic properties of IA can be associated with an apoptotic process [11,12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the highest TPC (542.2 mg GAE/g) and antioxidants activities (IC 50 = 4.94 µg/mL) were shown by the methanol extract as compared with other solvents (Table 4). The better extraction property of methanol was further supported by another study where methanol extract exhibited better anti-neoplastic effects as compared with other solvent extractions [47]. However, another study indicated that the use of ethyl acetate contributes to high antioxidant activities [48].…”
Section: Antioxidant Activities Of N Lappaceummentioning
confidence: 86%
“…Phytochemical analysis showed that the high antineoplastic effects of methanol peel extract were contributed by the high phenolic contents such as coumarin, flavonoid, phenols, saponin and tannin. Other compounds, such as alkaloid, carbohydrate, cardiac glycoside, protein, terpenoid and triterpenoid, were also detected in the methanol extract [47]. However, the anti-proliferative effect of peel and seed of the fruit tested on human mouth carcinoma cell line (CLS-354) showed that the peel (IC 50 = 292 µg/mL) and seeds (IC 50 = 305 µg/mL) did not show high anti-proliferative effects on the cancer cell lines [9].…”
Section: Other Biological Activities Of N Lappaceum 41 Anti-neoplastic Effectsmentioning
confidence: 98%